Suicide prevention program on suicidal behaviors and mental wellbeing among school aged adolescents: a scoping review - Nadeem Parpio, Yasmin; Nuruddin, Rozina; Ali, Tazeen Saeed; Mohammad, Nuruddin; Khan, Uzma Rahim; Shahzad, Salman; Khan, Murad Musa; Aslam, Mehreen (Frontiers in Public Health, 2025)
IntroductionSuicide is a significant public health concern among school-aged adolescents. This scoping review aimed to synthesize evidence-based literature on suicide prevention interventions designed to enhance mental wellbeing and reduce suicidal behavior in this population.MethodsFollowing the PRISMA-ScR guidelines and Arksey and O’ Malley’ s five-phase framework, a systematic search was conducted across five databases (PubMed, Psych Info, Google Scholar, Science Direct, EBSCO, and ProQuest) to identify relevant studies meeting the inclusion criteria. Key findings from 37 peer-reviewed papers on effective strategies and interventions were synthesized.ResultsThe reviewed studies encompassed diverse interventions, including school-based programs like Signs of Suicide (SOS) student training and digital platforms, as well as therapeutic and family-based approaches for school-age adolescents. Outcomes consistently demonstrated significant improvements in mental wellbeing, self-efficacy, and help-seeking behaviors. Furthermore, reductions in suicidal ideation and self-harm were observed across these interventions.DiscussionThe findings highlight the effectiveness of various suicide prevention interventions for school-aged adolescents. Future research should focus on integrating diverse and culturally sensitive school-based mental health services and risk screening programs, adapting interventions to align with specific cultural norms and values, particularly in low- and middle-income countries where research is lacking. Enhancing access to support and implementing resilience-building initiatives at the primary school level are crucial for empowering adolescents with essential help-seeking skills and resources, fostering a supportive environment for mental wellbeing and suicide prevention. A limitation of this review is the exclusion of non-peer-reviewed literature. Policymakers and school administrators should consider these findings when developing and implementing suicide prevention programs.Systematic review registrationThis review is registered in open science framework in 2022 ID: https://doi.org/10.17605/OSF.IO/6W8D9.